SELF-MEDICATION AMONG SECONDARY SCHOOL STUDENTS - Eduardo Solano Pina dos Santos; Camilla Moreira Andrade; Elena Bohomol (Universidade Federal do Paraná, 2019)
Objective: To gather data about the prevalence, drug classes, and main reasons for self-medication among secondary school students. Method: This was a descriptive cross-sectional study with 130 students from a state school in the municipality of São Paulo. Descriptive statistics, parametric, and nonparametric tests were used to analyze the data.Results: Students were between 13 and 20 years old, 91 (70%) were female and 112 (86.2%) practiced self-medication. Of these, 75 (67%) used medication for pain relief, 18 (16.1%) reported adverse reactions, and the most predominant drug class was pain relief medications, with 147 (59.2) mentions. Easy access to these products in drugstores was the main reason given by 49 (43.7%) participants. Conclusion: Education is important to deliver information to students and family members to discourage self-medication among this segment of the population.